Communication with caregivers about tumor genomic sequencing in childhood cancers. Issue 28 (1st October 2022) - Lee, Brittany M.; Bonkowski, Emily; Marron, Jonathan M; Barton, Krysta S.; Rosenberg, Abby R.
Abstract : 245 Background: Advances in genomic testing have the potential to improve the diagnosis, risk stratification, and targeted treatment of childhood cancers, and tumor genomic sequencing (TGS) at diagnosis is becoming standard of care. Nevertheless, little is known about how best to communicate information about the process and intent of TGS to patients and their caregivers, nor about discussion of TGS results and their implications. This demonstrates a glaring need, particularly given the already distressing time of a new diagnosis. Methods: This qualitative study included English-speaking caregivers (> 18yo) of children (< 18yo) with cancer (diagnosed 2mo-3yr prior), who had TGS sent at diagnosis. Caregivers completed a short demographic survey, and we extracted child medical data from the electronic health record. We conducted semi-structured, one-on-one interviews with participants about their experiences with and recommendations for communication about TGS at diagnosis. We transcribed the interviews verbatim and used Dedoose qualitative software to code the transcripts. We employed a conventional content approach for codebook development and used inductive coding, followed by deeper thematic analyses. Results: A total of 12 caregivers enrolled. Their median age was 39 years (range 32 – 52) and most were white (11, 92%), female (9, 75%), and had at least a bachelor's degree (8, 67%). Their children had leukemia (8, 67%), neuroblastoma (2, 17%), or brain tumors (2, 17%). Ten (83%) of the children had somatic findings on TGS, 3 (25%) of which prompted the recommendation for germline testing. On average, interviews lasted 36 minutes (19-46). We found two information-delivery themes, both of which underscored existing communication recommendations in pediatric oncology. (1) Caregivers experience informational and emotional overload at the time of their child's cancer diagnosis. The intensity of emotions negatively impacts information processing, and comprehension of information generally occurs best over time. Some parents described managing their emotions through eliciting more information. (2) Caregivers recommended a systematic delivery of information about TGS. Many preferred concise, direct information about TGS upfront, along with written information and opportunities to request more information over time. Some caregivers specifically cited the value of receiving information that would allow them to be "mentally prepared, " such as hearing about the potential for unexpected findings. Conclusions: Caregivers' preferences for communication about TGS at diagnosis fit within established communication practices in pediatric oncology. Given both the complexity and potential psychosocial impacts of TGS, particular attention to systematic, standardized but tailorable information delivery to caregivers about TGS is warranted.